King Soloman's Mines - "Haggard, H Rider" (Longman Group Ltd: China, 1995)
An elephant hunter's chronicle of his safari into the interior of South Africa to search for a fabled diamond mine and to rescue the brother of the English gentleman who accompanies him across the deserts and mountains
Keywords: English language - Readers - For schools